Strategic Utilization of Demographic Dividend to Build Resilient Defense Capabilities in Emerging Economies - Budiyanti, Fatwa; Hendra, Afrizal; Suryo, Almuchalif (Formosa Journal of Applied Sciences, 2025)
The purpose of this study is to analyze the Strategic Utilization of Demographic Dividends to Build Resilient Defense Capabilities in Developing Countries. The method used is Systematic Literature Review (SLR). The results show that to take advantage of the demographic dividend for defense, developing countries should focus on several key strategies. First, investing in education, particularly in STEM fields, is critical to building a skilled workforce for both the economic and defense sectors (Bloom et al., 2003). Managing the youth bulge by integrating young people into productive roles, including defense-related sectors such as cybersecurity and military technology, can help drive national security. Encouraging technological innovation through public-private partnerships will further strengthen defense capabilities. In addition, addressing the aging population by modernizing military infrastructure and increasing automation is critical for long-term defence readiness.